The impact of radiobiologically-informed dose prescription on the clinical benefit of yttrium-90 SIRT in colorectal cancer patients - Abbott, EM; Falzone, N; Lee, BQ; Kartsonaki, C; Winter, H; Greenhalgh, TA; McGowan, DR; Syed, N; Denis-Bacelar, AM; Boardman, P; Sharma, RA; Vallis, KA (Society of Nuclear Medicine and Molecular Imaging, 2020)
The purpose of this study was to establish the dose-response relationship of selective internal radiation therapy (SIRT) in patients with metastatic colorectal cancer (mCRC), when informed by radiobiological sensitivity parameters derived from mCRC cell lines exposed to yttrium-90 (90Y).